Brimstone & glory [videorecording (DVD)] (Oscilloscope Laboratories, 2018)
The National Pyrotechnic Festival in Tultepec, Mexico is a site of explosive festivity unlike any other in the world. In celebration of San Juan de Dios, patron saint of firework makers, conflagrant revelry engulfs the town for ten days. Artisans show off their technical virtuosity, up-and-comers create their own lo fi combustibles, and teams build larger-than-life papier-mache bulls to parade into the town square, adorned with fireworks that blow up in all directions.